2019
DOI: 10.3390/md17050285
|View full text |Cite
|
Sign up to set email alerts
|

Edaravone-Loaded Alginate-Based Nanocomposite Hydrogel Accelerated Chronic Wound Healing in Diabetic Mice

Abstract: Refractory wound healing is one of the most common complications of diabetes. Excessive production of reactive oxygen species (ROS) can cause chronic inflammation and thus impair cutaneous wound healing. Scavenging these ROS in wound dressing may offer effective treatment for chronic wounds. Here, a nanocomposite hydrogel based on alginate and positively charged Eudragit nanoparticles containing edaravone, an efficient free radical scavenger, was developed for maximal ROS sequestration. Eudragit nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 21 publications
0
42
0
1
Order By: Relevance
“…Edaravone, a commercial drug with the ability to scavenge •OH, is used to treat cerebral ischemia and has also been used in chronic wounds. The therapeutic effect was dosedependent, which proved the dual role of ROS in chronic wound healing (Fan et al, 2019). Ceria have also attracted attention as potential treatments for excessive-ROS-related diseases owing to their ability to mimic the activity of multiple antioxidant enzymes.…”
Section: Antioxidantmentioning
confidence: 97%
See 1 more Smart Citation
“…Edaravone, a commercial drug with the ability to scavenge •OH, is used to treat cerebral ischemia and has also been used in chronic wounds. The therapeutic effect was dosedependent, which proved the dual role of ROS in chronic wound healing (Fan et al, 2019). Ceria have also attracted attention as potential treatments for excessive-ROS-related diseases owing to their ability to mimic the activity of multiple antioxidant enzymes.…”
Section: Antioxidantmentioning
confidence: 97%
“…It has been proven that biomaterials and bioactive agents with antioxidative function, including diol-citrate esters, edaravone, and cerium dioxide, can accelerate chronic wound healing (Luo et al, 2004;Zhu et al, 2016;Speidel et al, 2017;Fan et al, 2019;Wu et al, 2019).…”
Section: Antioxidantmentioning
confidence: 99%
“…Delayed healing of skin ulcers is a complication of DM that is caused by diabetic microvascular disease and results in the failure of complete healing of skin wounds resulting in chronic ulcers, particularly in the lower limb [6]. Wound healing, or tissue repair, is a complex physiological process and involves several phases that include inflammation, cell proliferation, fibrosis, and remodeling that all depend on angiogenesis, which is the hallmark of granulation tissue [7].…”
Section: Introductionmentioning
confidence: 99%
“…It exists in the form of edaravone anion and can transfer electrons to oxygen-free radicals, thereby transforming free radicals into edaravone-free radicals [18]. In addition, it can inhibit peroxidation induced by lipid-and water-soluble peroxy radicals [19]. Various animal models have revealed that edaravone has neuroprotective effects [20].…”
Section: Discussionmentioning
confidence: 99%